Pengaruh perilaku ibu terhadap keikutsertaan program KB di kota medan tahun 2019 - Nopita Yanti Sitorus; R Maimunah (Holistik Jurnal Kesehatan, 2020)
Factors affecting participation of the family planning program in Medan, IndonesiaBackground: Family Planning is one of the most effective ways to increase family endurance and mother, children and women safety. In fact, there are many mothers who do not use contraception so as they have many children. Therefore, the distance between child births is very close.Purpose: Knowing of the effects of mothers’ behavior, attitude, and knowledge on their participation of the Family planning program in Medan in 2019.Method: A quantitative analytical method by cross sectional research design and conducted in 13 Public Health Centers (Puskesmas) and Maternity Clinics in Medan, North Sumatra Provinc, Indonesia. The population were 745 mothers of childbearing age and the samples were 260 mothers. The primary and secondary data were collected. They were analyzed by univariat and bivariate data analysis by using chi-square test with the level of confidence 95% .Results: The findings showed that mothers’ knowledge affect their participation in family planning program  with p=0,005 < 0,05. Mothers’ attitude affects their participation in the program with p=0,009 < 0,05. And mothers’ behavior affects their participation in the program with p=0,000 < 0,05Conclusion: This study proves that mothers’ participation in the family planning program in Medan is affected by knowledge, attitude, and behavior.Suggestion: The provincial health services authority to be cooperate with Board of Family Planning Program  in Medan in order to perform health promotions of Family Planning in terms of the use of appropriate contraceptive and prevention of early marriage. Health promotions by using counseling and health education are expected to improve mothers’ knowledge, to change their negative attitude, and to improve their behavior.Keywords: Behavior; Attitude; Knowlegde; Participation; Family Planning ProgramPendahuluan: Keluarga Berencana merupakan salah satu cara yang paling efektif untuk meningkatkan ketahanan keluarga, kesehatan, dan keselamatan ibu, anak, serta perempuan. Tetapi faktanya masih banyak ibu yang tidak menggunakan alat kontrasepsi sehingga memiliki banyak anak, dan jarak kelahiran yang dekat.Tujuan: Mengetahui faktor-faktor ibu terhadap keikutsertaan program Keluarga Berencana (KB).Metode: Penelitian kuantitatif dengan metode analitik menggunakan rancangan cross sectional, dilakukan di beberapa puskesmas dan rumah bersalin di kota Medan. Populasinya ibu pasangan usia subur sebanyak 745 orang dan sampel diperoleh sebanyak 260 orang. Data yang digunakan adalah data primer dan sekunder dan dianalisa secara univariat dan bivariat dengan menggunakan uji chi-square dengan tingkat kepercayaan 95%Hasil: Menunjukkan bahwa pengetahuan ibu berpengaruh terhadap keikutsertaan program KB, p=0,005 < 0,05. Sikap ibu berpengaruh terhadap keikutsertaan program KB, p=0,009 < 0,05 dan perilaku ibu berpengaruh terhadap keikutsertaan program KB, p=0,000 < 0,05.Simpulan: Penelitian ini membuktikan bahwa keikutsertaan ibu dalam program KB di Kota Medan dipengaruhi pengetahuan, sikap, dan perilaku.Saran: Dinas Kesehatan Kota Medan supaya dapat bekerjasama dengan BKKBN Kota Medan melakukan promosi kesehatan tentang Keluarga Berencana, penggunaan alat kontrasepsi yang sesuai, pencegahan pernikahan usia dini. Promosi kesehatan dengan penyuluhan atau pendidikan kesehatan diharapkan dapat meningkatkan pengetahuan, merubah sikap yang negatif menjadi positif,  dan meningkatkan tindakan menjadi lebih baik.